HIGH-TECH ALGORITHMS FOR VISUALIZATION OF SALT-DOME TECTONICS ON SEISMIC DATA - RUSACHENKO, Natalia; KUZMENKO, Pavlo (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Processing of seismic data, in the conditions of complex salt-dome tectonics of the Dnipro-Donetsk basin, requires special attention to the outline of the body of the salt shaft. The article is devoted to the analysis of methodological principles of applying high-tech seismic data processing algorithms, which have become industry standards in leading service geophysical companies, and in Ukraine are just beginning to be included in the seismic data processing workflow. The advantages of pre-stack depth migration compared to pre-stack time migration were described and one of them is absence of "pull up" and "push down" effects. In addition, the Reverse time migration (RTM) significantly improved the continuity of horizons, which is illustrated by data from the Dnieper-Donetsk basin. Full-waveform inversion (FWI) for visualizing the salt-dome tectonics and diapirs are described in detail. The integrated use of depth migration, RTM and FWI during the seismic data processing within the Romanian part of the Carpathians was considered. There is improvement of the resolution, the seismic horizons became more continuous, it bacame possible to avoid phase mismatch. Faults and salt bodies are also better visualized. Seismic data that maximally reflect the real geological environment can be obtained only as a result of a synergistic combination of perfect options for observation and processing systems, reliable velocity models, and modern migration algorithms as elements of technology in general. The complex application of these technologies demonstrates consistent geological results and creates prerequisites for the discovery of new deposits and hydrocarbon traps, which are confined to the zones of development of salt dome tectonics of the Dnipro-Donetsk basin.
Keywords: seismic processing; pre-stack depth migration; reverse time migration (RTM); full-waveform inversion (FWI)